2005
DOI: 10.1677/joe.1.06045
|View full text |Cite
|
Sign up to set email alerts
|

Developmental increases in plasma leptin binding activity and tissue Ob-Re mRNA expression in the rat

Abstract: Leptin's actions are mediated via the long form of its receptor, Ob-Rb, but access to this receptor on target cells is also influenced by truncated leptin receptor isoforms Ob-Ra and Ob-Re. Plasma leptin binding activity is primarily attributed to Ob-Re, which can restrict leptin passage to extravascular tissue. In this study we investigated whether plasma leptin binding activity changes from fetal to adult life in male and female rats, and whether tissue expression of Ob-Re mRNA changes during development. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The implication of this for leptin signaling is not clear, however, because plasma concentration of the soluble leptin receptor-e, which acts as a plasma binding protein that reduces leptin signaling, also is much higher in postpubertal male rats than postpubertal female rats (681).…”
Section: R1237 Sex Differences In the Physiology Of Eatingmentioning
confidence: 99%
“…The implication of this for leptin signaling is not clear, however, because plasma concentration of the soluble leptin receptor-e, which acts as a plasma binding protein that reduces leptin signaling, also is much higher in postpubertal male rats than postpubertal female rats (681).…”
Section: R1237 Sex Differences In the Physiology Of Eatingmentioning
confidence: 99%
“…Oestradiol is known to enhance leptin synthesis and to induce leptin gene expression in subcutaneous, perirenal and parametrial rat adipocytes . Another potential mechanism explaining sex differences in leptin responsiveness is the relatively greater binding to the soluble form of the leptin receptor in males relative to females, which results in lower leptin transport across the BBB . Although leptin is secreted principally by adipocytes, Wiesner et al have identified the brain as a producer of leptin by measuring of transcerebral leptin flux.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are at least six alternatively spliced isoforms of the leptin receptor (Lep-Ra, Rb, Rc, Rd, Re and Rf) in mice [7] , it is activation of Lep-Rb that is reported to be most involved in metabolic control. The shorter isoforms are thought to act as leptin transporters at different sites, including plasma and the blood-brain barrier [8,9] .…”
Section: Introductionmentioning
confidence: 99%